Bluesman: hibridismo entre música, videoclipe e cinema - Silva, Monyse Rayne Damasceno da (2023)
Focusing on relations between sound and image, this study stems from Bluesman - The film (2018), by director Douglas Bernardt, which proposes a hybrid discursive strategy, bringing music, music video and cinema closer, based on songs from the homonymous phonographic album by rapper Baco Exu do Blues. Considering as premises and theoretical reference works and concepts by authors who are related to the field in question - among others, Carol Vernallis, Rodrigo Oliva and Thiago Soares -, the analysis undertaken in this dissertation intends to contribute to such debate, building it around an intermedial method. As a hypothesis, the investigation follows in order to understand the concept of “cineclipe” related to short films language is situated between cinema and music video. Therefore, reflections on Bluesman - The film are given in three perspectives (corresponding to the three chapters of this work), namely: the film; the phonographic album; and the political discourse for the affirmation of black culture.